Compensation Information System Effect on Employees Performance in Oprong Sticker - Evelyn Lasmaida Manurung; Rubiatna Hardja; Ahmad Anas (Institute of Computer Science (IOCS), 2022)
Nowadays, the information system supports many activities to be more effective and efficient. One of its function is to make the workload becomes easier and faster. Compensation information system has purpose to give more accurate and insight about the data revealed in the project. The research has purpose to know about the current system and weaknesses on the program. Data collection conducted by using observation and interview method due to the problems and obstacles happening in Oprong Sticker. The suggestion of this research will be proposed to handle the current weakness and replace the old system to the new system also to develop administration system which leads to bring new environment of compensation process that respond faster service to employees later.